Effects of pre-partum and post-partum bolus injections of trace minerals on performance of beef cows and calves grazing native range - Mundell, Lauren Rae (Kansas State University, 2011)
Our objective was to evaluate the effects of pre- and post-partum bolus injections of a trace mineral solution on beef cow reproductive performance, body weight (BW) change, and body condition score (BCS) change and on performance of suckling calves. Mature beef cows (n = 460; initial BW = 497 ± 89 kg, initial BCS = 5.4 ± 0.74) were stratified by BCS, parity, and predicted calving date and assigned randomly to 1 of 2 treatments: 1) subcutaneous trace mineral (TM) injection containing 15 mg/mL Cu, 5 mg/mL Se, 10 mg/mL Mn, and 60 mg/mL Zn or 2) subcutaneous injection of physiological saline (SA). Injections were administered to cows (1 mL / 90 kg BW) 105 days before the first projected calving date and again 30 days before fixed-time AI. Calves received the same treatment as their dams and were injected (1 mL / 45 kg BW) at birth and again at 71 ± 21 days of age. Cows grazed native pastures for the duration of the study; trace mineral supplements and white salt were available to all cattle ad libitum before and during the study. Ovulation was synchronized using a 5-d CO-Synch + CIDR protocol and cows were inseminated 60 to 64 hours after CIDR removal. Cows were exposed to fertile bulls for natural-service breeding 10 days after AI for 35 to 50 days. Conception to AI and final pregnancy rate were assessed 36 days after AI with ultrasound and 120 days after AI via rectal palpation. Change in BW and BCS from initiation of the study to calving and from AI to weaning did not differ (P ≥ 0.15) between TM and SA cows. Conversely, TM cows had greater (P = 0.04) BCS increase than SA cows between calving and AI. Calf BW at birth, ADG, and age-adjusted weaning BW did not differ (P ≥ 0.36) between treatments. Proportion of cows with estrus cycles 17 and 8 days before ovulation synchronization was similar (P ≥ 0.51) between treatments. Conception to AI was greater (P = 0.05) for cows receiving TM (60.2%) than for cows receiving SA (51.2%); however, overall pregnancy did not differ (P = 0.24) between treatments and averaged 92%. Under the conditions of our study, pre- and post-partum TM injections improved conception to fixed-time AI by beef cows.
Keywords: Ruminant nutrition; Animal Sciences (0475)